Deconstructing Herding : Evidence from Pension Fund Investment Behavior - Raddatz, Claudio; Schmukler, Sergio L. (2012)
Pension funds have been expected to invest in a wide range of securities and provide liquidity to domestic capital markets since they are the most sophisticated investors, with plenty of resources to gather private information and manage portfolios professionally. However, by analyzing unique, monthly asset-level data from the pioneer case of Chile, this paper shows that pension funds tend to herd. This is consistent with pension funds copying each other in their investment strategies as a way to extract information, boost returns, and reduce risk. The authors compute measures of herding across asset classes (equities, government bonds, and private sector bonds) and at different pension fund industry levels. The results show that pension funds herd more in assets for which they have less market information and when risk increases. Moreover, herding is more prevalent across funds that narrowly compete with each other, that is, when comparing funds of the same type across pension fund administrators. There is much less herding within pension fund administrators and across pension fund administrators as a whole. This herding pattern is consistent with incentives for managers to be close to industry benchmarks, which might be driven by both market forces and regulation.